A Meta-Analysis Approach to Understanding Stress Response and Cross-Protection in Escherichia coli (Early view) - Maria Genesis M. Acosta; Gil M. Penuliar (Tropical Life Sciences Research, 2026)
Escherichia coli is a Gram-negative bacterium capable of causing gastrointestinal diseases and responding to various environmental stressors. Previous studies, however, are often insufficient in evaluating how antimicrobials, alcohols, oxidants, and osmotics affect the overall fitness of E. coli when exposed to secondary stress conditions. The objective of this study was to investigate the molecular mechanisms involved in the cross-protective response of E. coli to multiple stress factors, through a comprehensive meta-analysis of microarray datasets. Gene expression data were acquired from the GEO database. Datasets were screened and processed based on published inclusion criteria and methodologies. Unsupervised clustering methods using k-means and hierarchical algorithms were used to visualize the expression patterns of genes, and to compare the output of the algorithms. The expression of genes were considered as significantly different based on the following criteria: (a) a p-value < 0.05, (b) an FDR value < 0.05, and (c) a fold change > 2. Identified DEGs were further examined through in silico functional and pathway analyses. The stress response of E. coli involves the upregulation of genes related to GhoT/GhoS antitoxin/toxin system, SOS response, DNA damage and repair, cold and heat shock proteins, and phage shock proteins that protect cells from stress and cause tolerance to other types of stress. The metabolism of E. coli was also altered in response to stress. Some genes responsible for synthesizing and utilizing trehalose, cysteine, nucleoside monophosphate, vitamin B12 iron-sulfur cluster, and sulfur assimilation were significantly downregulated when exposed to unfavorable environments. Enriched pathways were identified in downregulated genes, which were related to metabolic pathways, biosynthesis of metabolites, and ABC transporters. These findings provide a comprehensive understanding of the molecular basis of cross-protection in E. coli, and suggest that metabolic shifts play a crucial role in the adaptation of E. coli to adverse environments.